Perancangan Buku Damar Kurung Gresik Dengan Teknik Vector Sebagai Upaya Mengenalkan Kebudayaan Kabupaten Gresik - Fithriyadi, Muhammad Nur; Riyanto, Darwin Yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
The purpose of the design book Timber Brackets Gresik is to introduce the culture of Gresik Regency. Further research is done using qualitative research methods that do interviews, observation, and literature to obtain data used to support the creation of design concepts book Timber Brackets Gresik. The data were analyzed by using multiple stages, namely the reduction of data, data presentation, and conclusion. After analyzing the data, the found a design concept or the keyword "Youthful". Description of "Youthful" is durable or have young spirit. The concept of "Youthful" aims to show that Thailand is an area that has a community spirit young. That is to say, the concept that really served to infuse the public perception that the public still has the old to Gresik spirit young. The result of the design of the book Timber brackets are to introduce the culture of Gresik Regency so that children and adolescents can recognise and continue the culture typical of Gresik Regency. Keywords: design, book illustration brackets, Timber, culture, Vector, Gresik.